Fiscal activism and the zero nominal interest rate bound - Sebastian Schmidt (European Central Bank (ECB), 2014)
I show that the zero nominal interest rate bound may render it desirable for society to appoint a fiscally activist policy-maker who cares less about the stabilisation of government spending relative to inflation and output gap stabilisation than the private sector does. I work with a simple New Keynesian model where the government has to decide each period afresh about the optimal level of public consumption and the one period nominal interest rate. A fiscally activist policy-maker uses government spending more aggressively to stabilise inflation and the output gap in a liquidity trap than an authority with preferences identical to those of society as a whole would do. The appointment of an activist policy-maker corrects for discretionary authorities' disregard of the expectations channel, thereby reducing the welfare costs associated with zero bound events.
Keywords: E52; E62; E63; 330; discretion; fiscal policy; monetary policy; zero nominal interest rate bound